Analisis produksi dan pendapatan petani kelapa dalam di Kecamatan Pengabuan Kabupaten Tanjung Jabung Barat - Khoirul Amin; Zulgani Zulgani; Purwaka Hari Prihanto (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
The purpose of this research is to find out and analyze the socio-economic characteristics of coconut farmers in Pengabuan Subdistrict and to analyze factors affecting the production and income of coconut farmers in Pengabuan Subdistrict in West Tanjung Jabung Regency.The method used this research is quantitative descriptive methode. The data used in this study is primary data. The analytical tool used is multiple linear regression. The results showed that at a significance level of 10% only land area variable had a significant effect on coconut production in Pengabuan Sub-District, Tanjung Jabung Barat District while labor, fertilizer and pest variables did not significantly influence the coconut production in Sub-District Pengabuan Tanjung Regency Jabung Barat. However, simultaneously the dependent variable significant influences of the production coconut in Pengabuan District, Tanjung Jabung Barat District. In terms of income, production, selling price, and management costs significantly influence the income of coconut farmers in Pengabuan District, both partially and simultaneousl in 10% significant level.